Mycobacterial Caseinolytic Protease Gene Regulator ClgR Is a Substrate of Caseinolytic Protease - Yoshiyuki Yamada (American Society for Microbiology, 2017)
ABSTRACT The mycobacterial caseinolytic protease ClpP1P2 is a degradative protease that recently gained interest as a genetically and pharmacologically validated drug target for tuberculosis. The first whole-cell active ClpP1P2 inhibitor, the human proteasome inhibitor bortezomib, is currently undergoing lead optimization to introduce selectivity for the bacterial target. How inhibition of ClpP1P2 translates into whole-cell antimicrobial activity is little understood. Previous work has shown that the caseinolytic protease gene regulator ClgR is an activator of the clpP1P2 genes and also suggested that this transcription factor may be a substrate of the protease. Here, we employ promoter activity reporters and direct mRNA level measurements showing that bortezomib treatment of Mycobacterium bovis BCG increased transcription of clpP1P2 and other ClgR-dependent promoters, suggesting that inhibition of ClpP1P2 increases cellular ClgR levels. Then, we carried out red fluorescent protein-ClgR fusion analyses to show that ClgR is indeed a substrate of ClpP1P2 and to identify ClgR’s C-terminal nonapeptide APVVSLAVA as the signal sufficient for recognition and efficient protein degradation by ClpP1P2. Interestingly, accumulation of ClgR appears to be toxic for bacilli, suggesting a mechanism for how pharmacological inhibition of ClpP1P2 protease activity by bortezomib translates into whole-cell antibacterial activity. IMPORTANCE With 9 million new cases and more than 1 million deaths per year, tuberculosis, caused by Mycobacterium tuberculosis, is the biggest infectious disease killer globally. New drugs for the treatment of the drug-resistant forms of the disease are needed. Recently, a new target-lead couple, the mycobacterial protease ClpP1P2 and the human anticancer drug bortezomib, was identified. However, we know little about how expression of this protease is regulated, which proteins in the bacterium it degrades, how the protease recognizes its target proteins, and how the inhibition of ClpP1P2 exerts whole-cell antimicrobial activity. Here, we show that the ClpP1P2 protease regulates its own expression, and we identified a new substrate and a new substrate recognition sequence and a mechanism for how ClpP1P2 inhibition causes bacterial growth inhibition.